Trends in residential segregation in the metropolis Latin American intermediate at the beginning of the XXI century. Porto Alegre (Brazil) and Córdoba (Argentina) (Revista LIDER, 2021)
This article presents the results of an investigation about the residential segregation in the cities of Porto Alegre /RS/Brazil and Córdoba/CO/Argentina, pointing the differences and similarities of this phenomenon, regarding the concept of the dual city. The analysis privileges the aspects that allow the comparison of the cities, considering their respective social characteristics. Taking the multidimensional conception of space, the variables of Demographics Censuses of Brazil (1991-2000) and Argentina (1991-2001) were used to construct some indicators that permit the evaluation of social differentiation in the cities. These indicators were submitted to factorial analysis and “cluster” techniques, whose results allowed the definition of the space-structuring patterns of Porto Alegre and Cordoba. In the conclusion the text shows a high level of similarities as well as the nonexistence of contrasts related to the impacts of globalization. It also shows that the urban expansion in both cities follows the lineaments of other Latin American metropolis, with a tendency towards social inequality between the two poles of urban population, in the last years. Such an inequality is not dual, but it presents itself in a fragmented form, with a diversifications of the social structure.